Negative-Value Property - Bruce R. Huber (Washington University Law Review, 2021)
Ownership is commonly regarded as a powerful tool for environmental protection and an essential solution to the tragedy of the commons. But conventional property analysis downplays the possibility of negative-value property, a category which includes contaminated, depleted, or derelict sites. Owners have little incentive to retain or restore negative-value property and much incentive to alienate it. Although the law formally prohibits the abandonment of real property, avenues remain by which owners may functionally abandon negative-value property, as demonstrated recently by busts in certain coal and oil & gas markets. When negative-value property is abandoned, whether formally or functionally, the rehabilitation of such property typically requires public expenditure—an externality which cuts against property’s general and salutary tendency to internalize spillovers at a low social cost. The existence of negative-value property, as well as its increasing abundance, reveals an underdeveloped aspect of property theory and a pressing need to fortify legal mechanisms that prevent abandonment and enforce owners’ financial responsibility for severely degraded property.
Keywords: Negative-value property; Property law; Abandoned property